2021
DOI: 10.1101/2021.09.15.460559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A histidine cluster determines YY1-compartmentalized coactivators and chromatin elements in phase-separated super-enhancers

Abstract: As an oncogenic transcription factor, Yin Yang 1 (YY1) regulates enhancer and promoter connection. However, gaps still exist in understanding how YY1 coordinates coactivators and chromatin elements to assemble super-enhancers. Here, we demonstrate that YY1 activates FOXM1 gene expression through forming liquid-liquid phase separation to compartmentalize both coactivators and enhancer elements. In the transactivation domain of YY1, a histidine cluster is essential for its activities of forming phase separation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The TFBSs for a total of 23 TFs were always enriched at anchors. These TFs include more universally-expressed regulators such as USF1/2 and SP1/2, as well as proteins involved in regulating 3D chromatin organization such as CTCF and YY1 [3,37,38]. However, we found that the large majority of these 165 TFs (n=130) have BSs that are enriched in a cell type-restricted fashion in non-anchor or all CM CREs.…”
Section: Resultsmentioning
confidence: 80%
“…The TFBSs for a total of 23 TFs were always enriched at anchors. These TFs include more universally-expressed regulators such as USF1/2 and SP1/2, as well as proteins involved in regulating 3D chromatin organization such as CTCF and YY1 [3,37,38]. However, we found that the large majority of these 165 TFs (n=130) have BSs that are enriched in a cell type-restricted fashion in non-anchor or all CM CREs.…”
Section: Resultsmentioning
confidence: 80%
“…The transcription factor YY1 is overexpressed in prostate [ 146 ], colon [ 147 ], liver [ 148 ], lung [ 149 ], and breast cancers [ 150 ], and its over-expression is associated with poor prognosis in patients with osteosarcoma and Acute Lymphoblastic Leukemia [ 151 , 152 ]. The histidine cluster in the AD of YY1 compartmentalizes BRD4, MED1, and enhancer elements in phase-separated condensates to activate FOXM1 expression in breast cancer [ 153 ]. Besides AD of TF, estrogen can bind to ligand-binding domains of estrogen receptor α (ERα) to form MED1 condensates [ 139 ].…”
Section: Phase Separation Model To Explain Features Of Super-enhancersmentioning
confidence: 99%